Pengaruh Likuiditas, Solvabilitas, Dan Profitabilitas Terhadap Nilai Perusahaan - Andita Novia Harfani; Dian Hakip Nurdiansyah (Journal of Economic, Bussines and Accounting (COSTING), 2021)
The purpose of this study is to determine and analyze whether Liquidity, Solvency and Profitability can affect either individually or simultaneously on firm value. The research method used in this research is descriptive analysis verification and the research instrument that is the object of observation in this study is the dependent variable or dependent variable (Y) is the firm value and the independent variables are: Liquidity: Current Ratio (X1 ), Solvency: Debt to Asset Ratio (X2), Profitability: Return on Assets (X3). The population used in this study are mining companies listed on the Indonesia Stock Exchange. A total of 39 mining companies. This research uses a sampling technique, namely purposive sampling. Mining companies that meet the purposive sampling criteria are 8 mining companies listed on the Indonesia Stock Exchange in 2015-2018. The results of this study are: Current Ratio has an effect and is significant on firm value but the Debt to Asset Ratio has no effect on firm value and return on assets has an effect and is significant on firm value. Simultaneously Current Ratio, Debt to Asset Ratio and Return on Assets have an influence on Company Value in mining companies for the 2015-2018 period. Keywords: CR, DAR, ROA, Company Value